2018
DOI: 10.1080/14992027.2018.1464216
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and work participation: a cross-sectional study in Norway

Abstract: Hearing loss seemed to influence work participation factors negatively; particularly, for moderate hearing loss and for women, even though the degree of employment was high. A lack of work place accommodation when there was a need for such was found. This implies increased attentiveness towards individual needs concerning the experienced disability a hearing loss may produce. A more frequent use of hearing disability assessment is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 38 publications
2
47
2
Order By: Relevance
“…However, the flexibility and accommodation by manager and coworkers tended to be restricted to task adjustments and occasional communication adaptations normally without the use of assistive listening devices. A cross-sectional study in Norway also found a low use of assistive listening devices (18.9%) additional to hearing aids among persons with hearing impairments in working age [14]. The same study also found that 30.7% reported to be in need of hearing related accommodation without receiving it.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the flexibility and accommodation by manager and coworkers tended to be restricted to task adjustments and occasional communication adaptations normally without the use of assistive listening devices. A cross-sectional study in Norway also found a low use of assistive listening devices (18.9%) additional to hearing aids among persons with hearing impairments in working age [14]. The same study also found that 30.7% reported to be in need of hearing related accommodation without receiving it.…”
Section: Discussionmentioning
confidence: 86%
“…An increased need for recovery with increased hearing loss was found in a cohort study [13], and a higher prevalence of hearing problems (hearing loss and/or tinnitus) was found among those with higher burnout scores [12]. Moreover, an elevated fatigue score among people with hearing loss of working age was found in a cross-sectional study [14]. The high levels of fatigue/exhaustion have been associated with the concentration and the hypervigilance, which employees with hearing impairments need in work settings [15].…”
Section: Introductionmentioning
confidence: 94%
“…Employees with mild to moderate hearing loss were found to use more energy in noise typical to open plan offices than their normal-hearing peers [30]. Moreover, moderate hearing loss was negatively associated with workability and fatigue in a crosssectional study in Norway [10]. Compared to mild hearing loss, moderate hearing loss was associated with an increased risk of a high fatigue score, high hearing disability score and a low workability score.…”
Section: Room For Improvementmentioning
confidence: 96%
“…High prevalence of fatigue or need for recovery after work in persons with hearing impairments has been established earlier [6,[8][9][10]. Hearing loss affects verbal communication with an impact on the ability to follow a conversation, particularly if unstructured and in background noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation